Erratum: Laparoscopic versus opengastric surgery for the treatment of pathological T1N0M0 gastric cancer in elderly patients: a matched study. Issue 1 (December 2017) - Pan, Haiyan; Li, Tao; Huang, Zhigang; Yu, Haibing; Kong, Danli; Ding, Yuanlin; Pan, Congcong; Jiang, Yugang
Abstract A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.